Prática pedagógica e planejamento educacional para uma jovem com deficiência intelectual matriculada na EJA - Leite, Graciliana Garcia (Universidade Federal de São Carlos, 2020)
This research had as main objectives to characterize the pedagogical practices of teachers of the regular classroom and of special education for youth and adults (EJA) and to elaborate and apply the individualized educational plan (PEI) in the context of the multifunctional resource room for a student with intellectual disability in EJA. The research was divided into 2 studies. Study 1 aimed to characterize the pedagogical practices of teachers in the regular classroom and special education who work with students with intellectual disabilities enrolled in EJA and their conceptions about PEI. Study 1 participants included a regular EJA classroom teacher and a special education teacher. Data collection was carried out based on observations from the multifunctional resource room and the regular classroom, and teachers responded to a semi-structured interview script. The instruments used were aimed at verifying aspects about the organization and development of pedagogical practices and the teachers' conception of the PEI. The research was carried out in a municipal school in the interior of São Paulo. The results identified a lack of understanding about the PEI and its functions in the school context and the difficulty of teachers in developing pedagogical practices suitable for young students and adults with intellectual disabilities. Study 2 had two objectives: (a) to identify the school demands and adaptive behavior of a student with intellectual disability enrolled in EJA and (b) to develop and apply the PEI for a student with intellectual disability in EJA, in partnership with the Teacher of special education. The research adopted the quantitative-qualitative approach carried out based on collaborative research. The study participants were a student with intellectual disabilities and a special education teacher. Study 2 was organized in three stages. In the first stage, semi-structured interviews were conducted with the target student's mother and the student, to assess the student, the Support Intensity Scale (SIS) and the School Skills Inventory were applied; in the second stage, the PEI was developed and applied in collaboration with the special education teacher, reflective meetings were held with the teacher to discuss and plan pedagogical practices, in addition to observations in the multifunctional resource room; in the third stage, the student was reevaluated and a semi-structured interview was conducted with the special education teacher, to check if there was any change in her pedagogical practices after the implementation of the PEI. The initial evaluations showed that the student had a significant deficit in relation to mathematics and needed adaptive support in activities related to the item that includes “lifelong learning”. The results indicated that the process of elaborating and implementing the PEI contributed to a better understanding of the special education teacher for the development of new pedagogical practices for young and adult students with intellectual disabilities and the interventions carried out in the PEI contributed to academic and adaptive development of the student.
Pedagogical practice and educational planning for a youth with intellectual disabilities enrolled in EJA
Keywords: Educação especial; Educação de jovens e adultos; Planejamento educacional individualizado; Prática pedagógica; Special education; Youth and adult education; Individual educational plan; Pedagogical practice; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO